Risk and Primary Commercial Lending In Ghana - Adoo, S. (University of Ghana, 1999)
It would be hard, if not impossible to overstress the importance of agriculture in the growth and development of Ghana's economy. Despite our concentrated efforts at industrialization, Ghana, like other African states, remains predominantly an agrarian society. Yet, despite agriculture's strategic role in the performance of the Ghanaian economy, financial institutions (especially commercial banks) have always shown a marked reluctance to plough funds into increasing the production and marketing of food, as demonstrated by the amount of credit extended to the agricultural sector. It is argued by Commercial banks that the agricultural sector is characterised by a greater risk vis-a-vis other sectors of the economy. Using risk and statistical analyses as employed by Okorie (1985) in a similar work, the study presents empirical evidence to refute this assertion. It concludes in particular that the risk characterising lending to the agricultural sector is not significantly higher than that identified with the other sectors of the Ghanaian economy during the years under review. And generally, that the risk elements of the entire economy have declined substantiaIIy for the three primary commercial banks, since the implementation of FINSAP. The study therefore recommends that commercial banks should increase their investment in the agricultural sector which will provide a bedrock to support the country's programme of accelerated growth.
MA in Agricultural Administration
Keywords: Basic disadvantages of commercial lending.; Importance of agriculture in the development of Ghana's economy; The risk agriculture sectors faces